Growth, luminescence, defects and scintillation properties of Sr co-doped LiI:Eu single crystal scintillator. (December 2021) - Kalyani,; Tyagi, Mohit; Singh, A.K.; Sonu,; Kumar, G. Anil
Abstract: To improve performance characteristics of Eu doped LiI single crystal scintillators for thermal neutron detection, single crystals having different concentrations of Sr co-doping were grown. One of the major disadvantages of these scintillators is the absence of any pulse shape discrimination of neutron and gamma radiations. Some degree of discrimination in these crystals could be introduced with the help of Sr co-doping. The effects of co-doping on crystal structure, electronic properties, defects, luminescence, self-absorption, and scintillation properties have been studied in detail. Graphical Abstract: ga1 Highlights: Single crystals of Sr co-doped LiI:Eu were grown by Bridgman furnace. The effect of co-doping on electronic, optical and scintilaltion properties was studied. The scintilation kinetics was tailored with the help of "Sr" co-doping. The "Sr" co-doping offers lower self-absorption and improves energy resolution. Co-doping introduces pulse shape discrimination properties to LiI:Eu scintillator.